The Ensemblist Nature of Plant Plurality - Yogi Hale Hendlin (Semiotic Review, 2020)
A core misconception about plants underlying much of the work in both plant studies and biology to currently revise it, is the designation of plants as quantifiable individuals rather than interspecies ensembles. Despite the epigenetics revolution in biology, ushering in the Extended Evolutionary Synthesis, plants and other organisms nonetheless are often observed as individual specimens with which one can tamper. In distinction to animals, which are fundamentally self-contained (even if both exosemiotically and endosemiotically their composition and signals are thoroughgoingly interspecies and elemental), plants disabuse us of the metaphysics of isolated ontologies through their radical plurality. In a mature forest, for example, it would be a mistake to cleanly demarcate where one plant ends and another begins, or were the plant ends and its fungal symbionts begin. The lessons of semiotic and thus ontological plurality and porosity plants tender also in fluctuating ways to alter our understanding of human and animal ontologies as plural.